Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1745-4549.2010.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drying Processes on Bioactive Phenolics, Vitamin C and Antioxidant Capacity of Red-Fleshed Apple Slices

Abstract: The impact of drying (air‐, oven‐ and vacuum‐drying) on bioactive polyphenolics, vitamin C and antioxidant capacity of slices of “Redfield” apple, a red‐fleshed apple cultivar, was investigated. The drying process significantly impacted the concentration of specific phenolic compounds and vitamin C concentration in dried slices. The loss of epicatechin, cyanidin‐3‐O‐galactoside, phloridzin and quercetin glycosides occurred during oven‐drying. The concentration of all the phenolic compounds in vacuum‐dried appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 26 publications
7
40
2
1
Order By: Relevance
“…These results demonstrate that oven drying causes the maximal reduction of the total antioxidant capacity of the apple peel ingredient. These results are in agreement with Joshi, Rupasinghe, and Khanizadeh (2011), who observed that the antioxidant capacity red-fleshed apple slices was significantly reduced by oven drying as compared to other drying methods (air and vacuum drying).…”
Section: Effect Of the Drying Methods On The Total Antioxidant Contentsupporting
confidence: 93%
“…These results demonstrate that oven drying causes the maximal reduction of the total antioxidant capacity of the apple peel ingredient. These results are in agreement with Joshi, Rupasinghe, and Khanizadeh (2011), who observed that the antioxidant capacity red-fleshed apple slices was significantly reduced by oven drying as compared to other drying methods (air and vacuum drying).…”
Section: Effect Of the Drying Methods On The Total Antioxidant Contentsupporting
confidence: 93%
“…However, no significant difference (p<0.05) was found between these method of preparations. Joshi et al (2009) reported similar retention of epigallocatechin, chlorogenic acid and quercetin glycosides in both freeze-dried and oven-dried 'Redfield' apple which could probably due to the stability of those phenolics in the sample. On the other hand, sun dried buds extract showed a significant lower antibacterial activity.…”
Section: Effect Of Drying Methodsmentioning
confidence: 60%
“…On the other hand, sun dried buds extract showed a significant lower antibacterial activity. Direct exposure of bioactive compounds to sunlight could facilitate oxidation process which correlated with the reduction of bioactivity (Joshi et al 2009). Besides, sun drying is commonly associated with prolonged drying times allow degradation of bioactive compounds by enzymatic reaction (polyphenol oxidase and glycosidase) (Shahidi & Naczk 2004).…”
Section: Effect Of Drying Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used traditional convective [5], microwave [6], vacuum [7], sublimation [8], and combined vacuum [9] drying and the combination of these techniques [10]. But such drying methods are quite expensive and energy-consuming.…”
Section: T L E V K і V S K Amentioning
confidence: 99%